Indications for surgery amongst new patients presenting to the paediatric ophthalmology unit of the University College Hospital, Ibadan (2021)
Objective: The objective of the study was to determine the proportion of children requiring ocular surgery amongst new patients presenting to the Paediatric Ophthalmology Unit of the University College Hospital, Ibadan, over a 2‑year period, to enhance planning and improve the efficiency of service delivery. Methods: The study was a retrospective review of records of all new patients aged 0–16 years who presented to the Paediatric Ophthalmology Unit of the University College Hospital, Ibadan, over a 2‑year period (May 2015–April 2017). Information on age and gender, clinical diagnosis and indications for surgery and type of surgery scheduled were retrieved from the diagnosis register of the unit, and a descriptive analysis was performed. Results: Of the 1240 children who presented to the clinic within the study period, 142 (11.5%) needed surgical interventions. Their ages ranged from 1 month to 16 years, with a mean age of 6.4 ± 4.7 years. Seventy‑nine (55.6%) of these were males. The most common indications for surgery were cataract and catara t‑related indications (n = 122, 85.9%), followed by glaucoma and strabismus. Other less common indications for surgery were nasolacrimal duct obstruction and epibulbar dermoid. Conclusion: Paediatric cataract, the leading cause of childhood blindness in this environment, presents the greatest surgical burden in our unit. It should, therefore, be a major focus of personnel training and equipment procurement for paediatric ophthalmology services in our environment.